Vers une prise en compte de la non-binarité dans l’enseignement du FLE - Éléonore de Beaumont (Recherches en didactique des langues et des cultures)
Non-binary people do not identify with the two normative poles of gender, masculine and feminine. In the context of learning FFL, they are confronted with the hypergrammatical and binary functioning of grammatical gender in French, which can be problematic when their first language does not have a grammatical gender, such as Turkish. How, then, can non-binary people be allowed to express themselves and talk about themselves in the FFL classroom? Based on a field survey conducted at Galatasaray University (Istanbul) in 2021-2022, this paper proposes an analysis of the issues related to the learning of non-binary people in FFL didactics, as well as pedagogical approaches.